Acetate Metabolism in Archaea: Characterization of an Acetate Transporter and of Enzymes Involved in Acetate Activation and Gluconeogenesis in Haloferax volcanii - Kuprat, Tom; Johnsen, Ulrike; Ortjohann, Marius; Schönheit, Peter (Frontiers in Microbiology, 2020)
The haloarchaeon Haloferax volcanii grows on acetate as sole carbon and energy source. The genes and proteins involved in uptake and activation of acetate and in gluconeogenesis were identified and analyzed by characterization of enzymes and by growth experiments with the respective deletion mutants. (i) An acetate transporter of the sodium: solute-symporter family (SSF) was characterized by kinetic analyses of acetate uptake into H. volcanii cells. The functional involvement of the transporter was proven with a Δssf mutant. (ii) Four paralogues AMP-forming acetyl-CoA synthetases that belong to different phylogenetic clades were shown to be functionally involved in acetate activation. (iii) The essential involvement of the glyoxylate cycle as an anaplerotic sequence was concluded from growth experiments with an isocitrate lyase knock-out mutant excluding the operation of the methylaspartate cycle reported for Haloarcula species. (iv) Enzymes involved in phosphoenolpyruvate synthesis from acetate, namely two malic enzymes and a phosphoenolpyruvate synthetase, were identified and characterized. Phylogenetic analyses of haloarchaeal malic enzymes indicate a separate evolutionary line distinct from other archaeal homologs. The exclusive function of phosphoenolpyruvate synthetase in gluconeogenesis was proven by the respective knock-out mutant. Together, this is a comprehensive study of acetate metabolism in archaea.